Speakers are more cooperative and less individual when interacting in larger group sizes - Pellegrino, Elisa; Dellwo, Volker (Frontiers in Psychology, 2023)
Cooperation, acoustically signaled through vocal convergence, is facilitated when group members are more similar. Excessive vocal convergence may, however, weaken individual recognizability. Therefore, constraints to convergence can arise in circumstances where interlocutors need to enhance their vocal individuality. Here, we tested the effects of group size (3 and 5 interactants) on vocal convergence and individualization in a social communication scenario in which individual recognition by voice is at stake. In an interactive game, players had to recognize each other through their voices while solving a cooperative task online. The vocal similarity was quantified through similarities in speaker i-vectors obtained through probabilistic linear discriminant analysis (PLDA). Speaker recognition performance was measured through the system Equal Error Rate (EER). Results revealed that vocal similarity between-speakers increased with a larger group size which indicates a higher cooperative vocal behavior. At the same time, there was an increase in EER for the same speakers between the smaller and the larger group size, meaning a decrease in overall recognition performance, which implies a decrease in vocal individualization. Taken together, these findings suggest that in larger groups of unacquainted speakers, ingroup cooperation and social cohesion through acoustic convergence have priority over individualization.